If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5y + -1(-3x) = 0 Remove parenthesis around (-3x) 3x + -5y + -1 * -3x = 0 Multiply -1 * -3 3x + -5y + 3x = 0 Reorder the terms: 3x + 3x + -5y = 0 Combine like terms: 3x + 3x = 6x 6x + -5y = 0 Solving 6x + -5y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5y' to each side of the equation. 6x + -5y + 5y = 0 + 5y Combine like terms: -5y + 5y = 0 6x + 0 = 0 + 5y 6x = 0 + 5y Remove the zero: 6x = 5y Divide each side by '6'. x = 0.8333333333y Simplifying x = 0.8333333333y
| 3a+b-(-2b)= | | 4a-5c+3a-c= | | 2a+3x-4x-5a= | | 9+b=c+3a | | -2(x-1)=-2x-(x+4) | | 9x-11-2x+4= | | x^2+y^2-12y=0 | | 2-10=z/-7 | | 3x-5y+4y+2x= | | 14x^2-24=0 | | 0=X^4-8x | | y-.333=2.66 | | -3(x-2)+4(x-7)=20 | | u+.333=.333 | | 4x+4(6x+3)= | | -0.55p-5=0.45 | | cosx/2-1=0 | | 7x^4+2x^2+21=0 | | -4-(2y-1)=-(3y+1) | | 21/4=8/t | | 4*(x+6)= | | X(-2)+18=50(-3x)+25 | | 2*(x+3)= | | 2*(3a)= | | -24+x=36 | | (-2x)+5+3x+-4x+(-1)+(-x)= | | 2x+(-2)=17 | | 6*2s=39 | | ×/3-4=×/5-6 | | 2(-1)+y=17 | | Y+12=c | | 3/7=n/21 |